Resin permeable composite material and preparation method thereof

By using glass powder and organic molding agent to prepare porous ceramic blanks, and perform resin penetration and pressurization curing, the problems of complex preparation process, high cost and poor hardness of existing dental ceramic resin composite materials are solved, and the material performance is achieved The stability and hardness of natural teeth are close to.

CN119461855APending Publication Date: 2025-02-18SHENZHEN XIANGTONG PHOTOELECTRIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574232.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The preparation process of existing dental ceramic resin composite materials has difficulty in process control, high preparation cost, unstable material performance, and the hardness is not close to the hardness of natural teeth.

Method used

The glass powder is mixed with an organic molding agent, and isostatically formed, and the ceramic blank with a porous structure is sintered. Then the coupling treatment is performed and the resin permeates under a vacuum environment. Finally, the resin is obtained by pressurizing and curing. Permeable composite material.

Benefits of technology

The preparation cost is reduced, the hardness is close to that of natural teeth, the material performance is more stable, the process is simplified, and the control is relatively easy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461855A_ABST
    Figure CN119461855A_ABST
Patent Text Reader

Abstract

The invention discloses a resin permeable composite material and a preparation method thereof, and the preparation method comprises the following steps: mixing glass powder with an organic forming agent, and carrying out dry pressing and isostatic pressing on the mixed material to obtain a biscuit body; placing the biscuit body in sintering equipment for sintering to obtain a ceramic body with a porous structure; carrying out coupling treatment on the ceramic body, putting the ceramic body subjected to the coupling treatment into a resin solution, and carrying out permeation in a vacuum environment, so as to obtain resin-permeated ceramic; and pressurizing and curing the resin-permeable ceramic to obtain the resin-permeable composite material. According to the preparation method of the resin permeable composite material provided by the invention, the glass powder has a transparent characteristic, so that compared with traditional zirconium oxide and aluminum oxide materials, the prepared green body is more natural and attractive, the hardness of the green body is closer to that of natural teeth, and a certain protection effect on abutment teeth is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dental restoration material preparation, and in particular to a resin infiltration composite material and a preparation method thereof. Background Art

[0002] Dental ceramic resin composite material is a high-performance biomedical material that combines the advantages of ceramic materials and resin matrix, and is widely used in the field of oral restoration. It can greatly shorten the processing efficiency of the processing end and the doctor end, and can be worn immediately after processing without sintering and excessive acid etching, greatly improving the doctor's operating efficiency and shortening the patient's waiting time.

[0003] The existing preparation method of dental ceramic resin includes:

[0004] Dry mixing method: After the ceramic powder and the resin matrix are dry mixed evenly, they are heated, melted or pressed to form. Advantages: The process is simple and easy to achieve large-scale production. Disadvantages: The dispersion may not be uniform enough, affecting the material properties.

[0005] Wet mixing method: ceramic powder is dispersed in the resin solution, stirred evenly, and then solidified. Advantages: good dispersion and can improve the uniformity of the material. Disadvantages: the preparation process is relatively complicated and bubbles may be introduced.

[0006] Impregnation method: Ceramic powder is filled into the resin matrix and then heated and cured. Advantages: Composite materials with complex structures can be prepared. Disadvantages: The process control is difficult and may affect the consistency of the material.

[0007] In-situ polymerization: ceramic powder is added to the resin monomer, and the polymerization reaction is initiated by an initiator to form a composite material. Advantages: It can achieve a good combination of ceramic powder and resin matrix. Disadvantages: The process control requirements are high and the reaction conditions need to be precisely controlled.

[0008] Nanocomposite technology: Use nano-grade ceramic powder and resin matrix to prepare nanocomposite materials through special processes. Advantages: Can significantly improve the strength and toughness of composite materials. Disadvantages: High preparation cost and high technical difficulty.

[0009] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0010] In view of the above-mentioned deficiencies in the prior art, the present invention provides a resin-infiltrated composite material and a preparation method thereof, aiming to reduce the production cost of dental ceramic resin and make the hardness of the prepared resin-infiltrated composite material closer to the hardness of natural teeth.

[0011] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0012] In a first aspect, a method for preparing a resin-infiltrated composite material comprises:

[0013] The glass powder is mixed with an organic forming agent, and the mixed material is dry pressed and isostatically pressed to obtain a green body;

[0014] placing the green body in a sintering device for sintering to obtain a ceramic body with a porous structure;

[0015] Performing a coupling treatment on the ceramic body, and placing the ceramic body after the coupling treatment in a resin solution, and performing infiltration under a vacuum environment to obtain a ceramic infiltrated with resin;

[0016] The resin-infiltrated ceramic is pressurized and cured to obtain the resin-infiltrated composite material.

[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0018] As a preferred technical solution, a method for preparing a resin-infiltrated composite material, wherein, in terms of mass percentage, the content of SiO2 and Al2O3 in the glass powder is greater than 80%; and the content of alkali metal oxide is less than 15%.

[0019] As a preferred technical solution, in the method for preparing a resin-infiltrated composite material, the average particle size of the glass powder is 3-10 microns.

[0020] As a preferred technical solution, in the method for preparing the resin-infiltrated composite material, the organic forming agent is polyvinyl alcohol; and the addition amount of the organic forming agent is 3-20% by weight.

[0021] As a preferred technical solution, a method for preparing a resin-infiltrated composite material, wherein the sintering temperature is 500-650° C. and the sintering time is 12-36 hours.

[0022] As a preferred technical solution, a method for preparing a resin-infiltrated composite material, wherein the types of resins in the resin solution include: triethylene glycol dimethacrylate, bisphenol A propylene glycol dimethacrylate, dimethacrylate carbamate, ethylene glycol dimethacrylate, and benzoyl peroxide.

[0023] As a preferred technical solution, in the method for preparing a resin-infiltrated composite material, the pressure of the dry pressing is 5-20 MPa; and the pressure of the isostatic pressing is 200-300 MPa.

[0024] As a preferred technical solution, a method for preparing a resin-infiltrated composite material, wherein the ceramic body after coupling treatment is placed in a resin solution and infiltrated under a vacuum environment, specifically comprising:

[0025] Placing the ceramic body in the resin solution, with the liquid level of the resin solution located at 1 / 2 of the height of the ceramic body, to perform the first infiltration;

[0026] placing the ceramic body after the first infiltration in the resin solution, with the liquid level of the resin solution located at 2 / 3 of the height of the ceramic body, and performing a second infiltration;

[0027] The ceramic body after the second infiltration is completely immersed in the resin solution and then infiltrated for the third time.

[0028] As a preferred technical solution, in the method for preparing a resin-infiltrated composite material, the pressure of the pressurized curing is 2-8 MPa and the curing temperature is 90-110°C.

[0029] In a second aspect, a resin-infiltrated composite material is provided, wherein the resin-infiltrated composite material is prepared by the preparation method described above.

[0030] Beneficial effects: Compared with the prior art, the preparation method of the resin infiltration composite material provided by the present invention has the inherent transparent property of glass powder. Compared with traditional zirconium oxide and aluminum oxide materials, the blank prepared by the present invention is more natural and beautiful, and the hardness is closer to the hardness of natural teeth, which plays a certain protective role on the abutment teeth. The use of vacuum infiltration can effectively control the infiltration process and reduce the complexity of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention provides a schematic flow chart of a method for preparing a resin infiltrated composite material. DETAILED DESCRIPTION

[0032] The present invention provides a resin infiltration composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementation methods. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and do not mean a necessary sequence, unless otherwise specified that a certain sequence must be followed. The serial numbers themselves, such as "first", "second", etc., assigned to the components herein are only used to distinguish the objects described and do not have any order or technical meaning.

[0034] The inventors have found that the preparation processes of most existing dental ceramic resin composite materials have the problems of difficult process control, high preparation costs, unstable performance of the prepared products, and differences in material hardness from the hardness of natural teeth.

[0035] In order to solve the above problems, the inventors of the present invention provide a resin infiltration composite material and a preparation method thereof. The preparation method adopts glass powder as raw material, and the green body prepared by the method is more natural and beautiful, and the hardness is closer to the hardness of natural teeth, which plays a certain protective role on the abutment teeth. The resin vacuum infiltration method is adopted, and the resin raw materials are mixed and infiltrated into the prepared ceramic green body by vacuum infiltration. The ceramic green body is formed by mixing glass powder and organic forming agent, pressing and sintering, and is characterized by porous channels, which facilitates the infiltration of resin. After the resin is infiltrated, the material is thermally cured as a whole to complete the preparation of the material. The preparation process is simplified.

[0036] like Figure 1 As shown, the present invention provides a method for preparing a resin-infiltrated composite material, comprising the following steps:

[0037] S10, mixing the glass powder with the organic forming agent, and performing dry pressing and isostatic pressing on the mixed material to obtain a green body.

[0038] Specifically, a glass substrate with a SiO2 and Al2O3 content greater than 80% and an alkali metal oxide content less than 15% is selected, the glass substrate is melted at a temperature of 1500-1700°C, and after melting, it is quenched in high-temperature water to form a glass slag material, and the water-quenched slag material is refined and graded, and the final glass powder particle size is required to be 1-50 microns, with an average particle size controlled at 3-10 microns, preferably 5-8 microns), to ensure the sintering performance and molding performance of the base material, while ensuring sufficient discharge of the molded organic matter.

[0039] In the present invention, the organic forming agent includes but is not limited to polyvinyl alcohol (PVA); the addition amount of the organic forming agent can be 3% to 5%, 5% to 7%, 7% to 9%, 9% to 11%, 11% to 12%, 12% to 14%, 14% to 16%, 16% to 18%, 18% to 20%. The mixed material is subjected to dry pressing and isostatic pressing, with a dry pressing pressure of 5-20Mpa, preferably 8-15Mpa, and a pressure holding time of 5-20min. The isostatic pressing pressure is 200-300Mpa, preferably 240-280Mpa, and the pressure holding time is 30-180min. The green body can be initially formed by dry pressing, providing a certain strength and shape, and then the density and uniformity of the green body can be further improved by isostatic pressing; after dry pressing, isostatic pressing can eliminate the uneven density and pores generated during the dry pressing process and reduce defects; isostatic pressing can improve the mechanical strength of the green body, making it more suitable for subsequent processing and use.

[0040] S20, placing the green body in a sintering device for sintering to obtain a ceramic body with a porous structure.

[0041] Specifically, the element ligand is placed in a sintering furnace for sintering, and the sintering temperature is controlled at 500-650°C. Too high a temperature will cause the glass powder to melt and produce closed pores, and too low a temperature is not conducive to the volatilization of organic matter. The sintering time is 12-36 hours. After sintering, a porous structure is formed inside the blank due to the volatilization of the organic forming agent. At the same time, since the glass powder is used as the base material, it has good air permeability when the organic forming agent volatilizes.

[0042] S30, performing a coupling treatment on the ceramic body, and placing the ceramic body after the coupling treatment in a resin solution, and performing infiltration under a vacuum environment to obtain a resin-infiltrated ceramic.

[0043] Specifically, the sintered ceramic body is placed in a solution of a coupling agent so that the coupling agent forms a chemical bond on the surface of the ceramic body. The ceramic body after the coupling treatment is dried so that the coupling agent is firmly combined with the surface of the ceramic body. The ceramic body after the coupling treatment can be better combined with a resin. Among them, the resin used includes but is not limited to triethylene glycol dimethacrylate, bisphenol A propylene glycol dimethacrylate, dimethacrylate carbamate, ethylene glycol dimethacrylate, and benzoyl peroxide.

[0044] In this embodiment, the infiltration is performed under a vacuum environment, and the ceramic body is placed in the resin solution, the liquid level of the resin solution is located at 1 / 2 of the height of the ceramic body, and the infiltration time is 6-12 hours, and the first infiltration is performed; the ceramic body after the first infiltration is placed in the resin solution, the liquid level of the resin solution is located at 2 / 3 of the height of the ceramic body, and the infiltration time is 6-12 hours, and the second infiltration is performed; the ceramic body after the second infiltration is completely immersed in the resin solution, and the infiltration time is 12-72 hours, and the third infiltration is performed. By adopting multiple infiltrations, the resin solution can be better infiltrated into the interior of the ceramic body, and the infiltration is more uniform.

[0045] S40, pressurizing and curing the resin-infiltrated ceramic to obtain the resin-infiltrated composite material.

[0046] Specifically, the ceramic body after vacuum infiltration is pressurized and cured at a pressure of 2-8 MPa and a curing temperature of 90-110° C. Pressurized curing prevents volume shrinkage during the resin curing process (volume shrinkage can cause separation of the two phases and obvious defects).

[0047] Based on the same inventive concept, the present invention also provides a resin-infiltrated composite material, which is prepared by the above-mentioned preparation method. Compared with traditional zirconium oxide and aluminum oxide materials, the blank prepared by the resin-infiltrated composite material is more natural and beautiful, and its hardness is closer to that of natural teeth, which plays a certain protective role on the abutment teeth.

[0048] The resin infiltration composite material and the preparation method thereof provided by the present invention are further explained below through specific preparation examples.

[0049] Example 1

[0050] 1. Preparation of glass blank

[0051] 1.1 Mixing of glass raw materials: by mass percentage: 56% silicon dioxide, 25% aluminum hydroxide, 6% potassium carbonate, 10% sodium carbonate, 3% other raw materials. Weigh 500g of raw materials, put them into a mixer, and mix them for 1 hour to ensure that the raw materials are fully mixed.

[0052] 1.2 Preparation of glass powder: (Pour the mixed raw materials into a zirconium quartz crucible, put the crucible into a high-temperature furnace, heat it to 1600°C at a heating rate of 10°C / min, and then keep it warm for 1 hour to completely melt the raw materials. After melting, take out the crucible at a high temperature of 1300°C and quickly pour out the glass liquid for water quenching to form glass slag. The water-quenched slag is refined by a roller mill (refining requirements are below 100 mesh), and then processed by a jet mill and a classifier (to remove powder below 1 micron). The average particle size of the prepared powder is 7.6 microns, and D97 is 28.3 microns.

[0053] 1.3 Preparation of glass blank; (1) Prepare PVA aqueous solution (water bath at 90°C, stirring for 12h), prepare 100g PVA aqueous solution at a mass fraction of 10%. (2) Take 100g of the glass powder mentioned in 1.2, mix it evenly with 100g PVA aqueous solution, and then dry the mixture at a drying temperature of 100°C and keep it warm for 2h to obtain the dried material. Then dry press the dried material at a pressure of 8Mpa and keep the pressure for 10min. After molding, take out the material and vacuum seal it, then put it into an isostatic press at a pressure of 220Mpa and keep the pressure for 30min. Finally, the glass blank is obtained.

[0054] 1.4 Sintering of the green body: Place the green body described in 1.3 into a sintering furnace, heat the temperature to 520°C at a heating rate of 2°C / min, keep the temperature for 12 hours, and then naturally cool down to room temperature to complete the sintering of the green body.

[0055] 2. Pretreatment of ceramic green body: (1) Preparation of coupling agent: Take 45 ml of distilled water, 45 ml of alcohol, 3 ml of KH570, stir at room temperature for 1 hour, then add acetic acid to adjust the pH to 3.2 to obtain coupling agent solution. (2) Half-immerse the green body described in 1.4 into the coupling agent solution, put it into a vacuum drying oven with a vacuum degree of -0.1 MPa, and keep it for 6 hours. Then add the coupling agent solution again to completely immerse the green body, maintain the vacuum degree of -0.1 MPa, and continue to keep it for 6 hours. After the infiltration is completed, take out the green body and put it into a drying oven for drying, the drying temperature is 105°C, and the drying time is 2 hours. After cooling, take it out to complete the pretreatment of the ceramic green body.

[0056] 3. Mixing and preparation of resin: According to the mass percentage: 20% Bis-GAM, 50% TEGDMA, 30% UDMA, weigh 200 grams of raw materials, add 1.2% BPO. Dissolve the raw materials and mix them evenly. Mixing conditions: stir in a 45℃ water bath for 12 hours. Get a well-mixed resin solution.

[0057] 4. Vacuum infiltration of resin (divided into multiple small amounts of infiltration, the first time the resin is added to 1 / 2 of the height of the blank, the infiltration time is 10 hours, the second time the resin is added to 2 / 3, the infiltration time is 12 hours, the third time the resin is added until it is completely immersed, the infiltration time is 12 hours), the vacuum degree throughout the process is -0.5Mpa.

[0058] 5. After the infiltration is completed, pressurized curing is carried out (to prevent volume shrinkage during the resin curing process, which will lead to separation of the two phases and obvious defects). The pressure in the curing chamber is 5Mpa, the curing temperature is 100℃, and the curing time is 6h. After the curing is completed, the final product is obtained.

[0059] Example 2

[0060] 1. Preparation of glass blank

[0061] 1.1 Mixing of glass raw materials: by mass percentage: 60% silicon dioxide, 25% aluminum hydroxide, 7% potassium carbonate, 6% sodium carbonate, 2% other raw materials. Weigh 500g of raw materials, put them into a mixer, and mix them for 1 hour to ensure that the raw materials are fully mixed.

[0062] 1.2 Preparation of glass powder: (Pour the mixed raw materials into a zirconium quartz crucible, put the crucible into a high-temperature furnace, heat it to 1600°C at a heating rate of 8°C / min, and then keep it warm for 1.5 hours to completely melt the raw materials. After melting, take out the crucible at a high temperature of 1300°C and quickly pour out the glass liquid for water quenching to form glass slag. The water-quenched slag is refined by a roller mill (refining requirements are below 100 mesh), and then processed by a jet mill and a classifier (to remove powder below 1 micron). The average particle size of the prepared powder is 7.6 microns, and D97 is 28.3 microns.

[0063] 1.3 Preparation of glass blank; (1) Prepare PVA aqueous solution (water bath at 90°C, stirring for 12h), prepare 100g PVA aqueous solution at a mass fraction of 3%. (2) Take 100g of the glass powder mentioned in 1.2 and mix it evenly with 100g PVA aqueous solution, then dry the mixture at a drying temperature of 100°C and keep it warm for 2h to obtain the dried material. Then dry press the dried material at a pressure of 5Mpa and keep the pressure for 10min. After molding, take out the material and vacuum seal it, then put it into an isostatic press at a pressure of 200Mpa and keep the pressure for 30min. Finally, the glass blank is obtained.

[0064] 1.4 Sintering of the green body: Place the green body described in 1.3 into a sintering furnace, raise the temperature to 500°C at a heating rate of 2°C / min, keep the temperature for 15 hours, and then naturally cool down to room temperature to complete the sintering of the green body.

[0065] 2. Pretreatment of ceramic green body: (1) Preparation of coupling agent: Take 45 ml of distilled water, 45 ml of alcohol, and 3 ml of KH570, stir at room temperature for 1 hour, then add acetic acid to adjust the pH to 3.2 to obtain a coupling agent solution. (2) Half-immerse the green body described in 1.4 into the coupling agent solution, put it into a vacuum drying oven with a vacuum degree of -0.1 MPa, and keep it for 6 hours. Then add the coupling agent solution again to completely immerse the green body, maintain the vacuum degree of -0.1 MPa, and continue to keep it for 6 hours. After the infiltration is completed, take out the green body and put it into a drying oven for drying, the drying temperature is 105°C, and the drying time is 2 hours. After cooling, take it out to complete the pretreatment of the ceramic green body.

[0066] 3. Mixing and preparation of resin: According to the mass percentage: 20% Bis-GAM, 50% TEGDMA, 30% UDMA, weigh 200 grams of raw materials, add 1.2% BPO. Dissolve the raw materials and mix them evenly. Mixing conditions: stir in a 45℃ water bath for 12 hours. Get a well-mixed resin solution.

[0067] 4. Vacuum infiltration of resin (divided into multiple small amounts of infiltration, the first time the resin is added to 1 / 2 of the height of the blank, the infiltration time is 10 hours, the second time the resin is added to 2 / 3, the infiltration time is 12 hours, the third time the resin is added until it is completely immersed, the infiltration time is 12 hours), the vacuum degree throughout the process is -0.5Mpa.

[0068] 5. After the infiltration is completed, pressurized curing is carried out (to prevent volume shrinkage during the resin curing process, which will lead to separation of the two phases and obvious defects). The pressure in the curing chamber is 2Mpa, the curing temperature is 90℃, and the curing time is 6h. After the curing is completed, the final product is obtained.

[0069] Example 3

[0070] 1. Preparation of glass blank

[0071] 1.1 Mixing of glass raw materials: by mass percentage: 67% silicon dioxide, 15% aluminum hydroxide, 8% potassium carbonate, 8% sodium carbonate, 2% other raw materials. Weigh 500g of raw materials, put them into a mixer, and mix them for 1 hour to ensure that the raw materials are fully mixed.

[0072] 1.2 Preparation of glass powder: (Pour the mixed raw materials into a zirconium quartz crucible, put the crucible into a high-temperature furnace, heat it to 1600°C at a heating rate of 8°C / min, and then keep it warm for 1.5 hours to completely melt the raw materials. After melting, take out the crucible at a high temperature of 1300°C and quickly pour out the glass liquid for water quenching to form glass slag. The water-quenched slag is refined by a roller mill (refining requirements are below 100 mesh), and then processed by a jet mill and a classifier (to remove powder below 1 micron). The average particle size of the prepared powder is 7.6 microns, and D97 is 28.3 microns.

[0073] 1.3 Preparation of glass blank; (1) Prepare PVA aqueous solution (water bath at 90°C, stirring for 12h), prepare 100g PVA aqueous solution at a mass fraction of 20%. (2) Take 100g of the glass powder mentioned in 1.2, mix it evenly with 100g PVA aqueous solution, and then dry the mixture at a drying temperature of 100°C and keep it warm for 2h to obtain the dried material. Then dry press the dried material at a pressure of 20Mpa and keep the pressure for 5min. After molding, take out the material and vacuum seal it, then put it into an isostatic press at a pressure of 300Mpa and keep the pressure for 20min. Finally, the glass blank is obtained.

[0074] 1.4 Sintering of the green body: Place the green body described in 1.3 into a sintering furnace, raise the temperature to 650°C at a heating rate of 2°C / min, keep the temperature for 36 hours, and then cool naturally to room temperature to complete the sintering of the green body.

[0075] 2. Pretreatment of ceramic green body: (1) Preparation of coupling agent: Take 45 ml of distilled water, 45 ml of alcohol, and 3 ml of KH570, stir at room temperature for 1 hour, then add acetic acid to adjust the pH to 3.2 to obtain a coupling agent solution. (2) Half-immerse the green body described in 1.4 into the coupling agent solution, put it into a vacuum drying oven with a vacuum degree of -0.1 MPa, and keep it for 6 hours. Then add the coupling agent solution again to completely immerse the green body, maintain the vacuum degree of -0.1 MPa, and continue to keep it for 6 hours. After the infiltration is completed, take out the green body and put it into a drying oven for drying, the drying temperature is 105°C, and the drying time is 2 hours. After cooling, take it out to complete the pretreatment of the ceramic green body.

[0076] 3. Mixing and preparation of resin: According to the mass percentage: 20% Bis-GAM, 50% TEGDMA, 30% UDMA, weigh 200 grams of raw materials, add 1.2% BPO. Dissolve the raw materials and mix them evenly. Mixing conditions: stir in a 45℃ water bath for 12 hours. Get a well-mixed resin solution.

[0077] 4. Vacuum infiltration of resin (divided into multiple small amounts of infiltration, the first time the resin is added to 1 / 2 of the height of the blank, the infiltration time is 10 hours, the second time the resin is added to 2 / 3, the infiltration time is 12 hours, the third time the resin is added until it is completely immersed, the infiltration time is 12 hours), the vacuum degree throughout the process is -0.5Mpa.

[0078] 5. After the infiltration is completed, pressurized curing is carried out (to prevent volume shrinkage during the resin curing process, which will lead to separation of the two phases and obvious defects). The pressure in the curing chamber is 8Mpa, the curing temperature is 110℃, and the curing time is 6h. After the curing is completed, the final product is obtained.

[0079] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a resin-infiltrated composite material, characterized in that: include: The glass powder is mixed with an organic forming agent, and the mixed material is dry pressed and isostatically pressed to obtain a green body; placing the green body in a sintering device for sintering to obtain a ceramic body with a porous structure; Performing a coupling treatment on the ceramic body, and placing the ceramic body after the coupling treatment in a resin solution, and performing infiltration under a vacuum environment to obtain a ceramic infiltrated with resin; The resin-infiltrated ceramic is pressurized and cured to obtain the resin-infiltrated composite material.

2. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: In terms of mass percentage, the content of SiO2 and Al2O3 in the glass powder is greater than 80%; the content of alkali metal oxide is less than 15%.

3. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The average particle size of the glass powder is 3-10 microns.

4. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The organic forming agent is polyvinyl alcohol; the addition amount of the organic forming agent is 3-20% by weight.

5. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The sintering temperature is 500-650°C; the sintering time is 12-36h.

6. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The types of resins in the resin solution include: triethylene glycol dimethacrylate, bisphenol A propylene glycol dimethacrylate, dimethacrylate urethane, ethylene glycol dimethacrylate, and benzoyl peroxide.

7. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The dry pressing pressure is 5-20 MPa; the isostatic pressing pressure is 200-300 MPa.

8. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The step of placing the ceramic body after the coupling treatment in a resin solution and infiltrating the resin solution under a vacuum environment specifically includes: Placing the ceramic body in the resin solution, with the liquid level of the resin solution located at 1 / 2 of the height of the ceramic body, to perform the first infiltration; placing the ceramic body after the first infiltration in the resin solution, with the liquid level of the resin solution located at 2 / 3 of the height of the ceramic body, and performing a second infiltration; The ceramic body after the second infiltration is completely immersed in the resin solution and then infiltrated for the third time.

9. The method for preparing a resin-infiltrated composite material according to claim 1, characterized in that: The pressure of the pressurized curing is 2-8 MPa; the curing temperature is 90-110°C.

10. A resin-infiltrated composite material, characterized in that: The resin-infiltrated composite material is prepared by the preparation method according to any one of claims 1 to 9.